PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN CANVA DI KELAS V SDN 02 PEKAN SELASA SOLOK SELATAN - Nursella; Yesi Anita; Rahmatina; Hasmai Bungsu Ladiva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this research is to describe the improvement of learning outcomes of Pancasila Education using the Problem Based Learning model assisted by Canva in class V SDN 02 Pekan Selasa Solok Selatan. This study applies the type of Classroom Action Research (CAR) using qualitative and quantitative approaches. The subjects in this study were teachers (researchers) and students totaling 22 students consisting of 14 males and 8 females. The results of this study showed an increase in: a) cycle I teaching modules with an average of 85.41% (Good) and cycle II 95.83% (Very Good), b) implementation in the teacher aspect of cycle I with an average of 87.49% (Good) and cycle II 96.42% (Very Good), while the implementation in the student aspect of cycle I obtained an average of 85.71% and cycle II 96.42% (Very Good), c) assessment of students in improving learning outcomes in cycle I obtained an average of 76.59% and cycle II with an average of 85.19%. Based on these results, it can be concluded that the Problem Based Learning model assisted by Canva can improve learning outcomes of Pancasila Education in class V.